Indentificación de necesidades educativas especiales, e incidencia de las misma en el rendimiento escolar de los estudiantes de 4° año de EGB de la Escuela Manuel Sigiberto Loayza de la parroquia urbana la Susaya, cantón Piñas, en el periodo lectivo 2012-2013. - Campoverde Campoverde, Senovia Chanena (2013)
Identification of special educational needs, and impact thereof on the academic performance of students of 4th year of EGB school Sigiberto Manuel Loayza urban parish The Susaya, Piñas Canton, in the academic year 2012-2013 Basque explain through the hypothesis that the lack of knowledge and training of teachers at the school indicated, not allow them to quickly identify the presence of NEE, let alone address them properly and this adversely affects the academic performance of students in the fourth year EGB school said.